Schnella madeleinae (Leguminosae: Cercidoideae), a new species with entire leaves from the Magdalena River Valley of Colombia - Casas-Restrepo, Luis Carlos; Fonseca-Cortés, Andrés; Paganucci De Queiroz, Luciano; Ribeiro Dos Santos, Francisco De Assis (Phytotaxa, 2023)
Schnella madeleinae, a new species of liana with entire leaves from the Magdalena River Valley of Colombia, is described, illustrated, and aspects related to its distribution, conservation status, and relationships with morphologically similar species are discussed. Schnella madeleinae is characterized by the presence of heteromorphic petals in which the three superior petals are wider (4.5–5.0 × 2.5–3.0 mm) with respect to the two inferiors (5–6 × 2.0–2.5 mm) and oblong laterally compressed legumes of 5.0–6.5 × 1–2 cm. This new species is only known from five localities in the departments of Antioquia and Bolivar. Additionally, a key to the species of the entire leaves of the Schnella sect. Schnella is presented.